Preparation method and application of sodium alginate / bacterial cellulose composite aerogel fiber

CN122879853APending Publication Date: 2026-10-09INNER MONGOLIA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610638279.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

并且,由于其内部泡沫溶液密度极低,当其进入凝固浴溶液后会不可控的向上漂浮、卷曲,不利于纤维收集

Benefits of technology

[0021]本发明的有益效果在于:本发明提供了一种海藻酸钠/细菌纤维素复合气凝胶纤维的制备方法及其应用,本发明制备的气凝胶长纤维具有复杂的三维网络骨架;通过检测,本发明制备的气凝胶长纤维具有高达305 m2/g的高比表面积,并且其孔径主要分布在30~40 nm区间;该特性使得利用本发明制备的复合气凝胶纤维能够编织为纺织品后,具有高保温性。通过打结测试和实际编织验证了其可编织性能;通过径向压缩-回弹的测试,验证了本发明复合气凝胶纤维具有优异的径向弹性。通过保温性能测试,验证了本发明复合气凝胶纤维编织的纺织品具有稳定的保温隔热能力。综合以上性能,本发明复合气凝胶纤维可以用作服装面料使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879853A_ABST
    Figure CN122879853A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of sodium alginate / bacterial cellulose composite aerogel fibers and application thereof, and belongs to the field of aerogel composite materials; the prepared aerogel long fibers have a complex three-dimensional network skeleton; through detection, the prepared aerogel long fibers have a high specific surface area of 305 m 2 / g, and the pore diameter mainly distributes in the interval of 30-40 nm; the property makes the composite aerogel fibers prepared by using the application have high heat preservation after being woven into textiles. The knotted test and actual weaving verify the weavability of the composite aerogel fibers; through the radial compression-rebound test, it is verified that the composite aerogel fibers have excellent radial elasticity. Through the heat preservation performance test, it is verified that the textiles woven by the composite aerogel fibers have stable heat preservation and insulation capacity. In combination of the above performances, the composite aerogel fibers can be used as clothing fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aerogel composite materials, and particularly to a method for preparing sodium alginate / bacterial cellulose composite aerogel fibers and their applications. Background Technology

[0002] Existing technology, Chinese invention patent CN121065856B, discloses a method for preparing radially highly elastic aerogel fibers. In this method, radially highly elastic aerogel fibers are prepared by coaxial spinning. The preparation process is limited by the flow state of the inner-axis foaming solution. When the foaming solution flows through the inner-axis needle, the bubbles are inevitably compressed. Due to the toughness of the liquid film, the bubbles do not rupture, and they quickly return to their original shape after being squeezed out of the needle. This potential energy release from "compression-recovery" results in the outer shell of the hydrogel fiber bearing significant pressure during coaxial spinning. Furthermore, due to the extremely low density of the internal foam solution, it floats and curls uncontrollably upon entering the coagulation bath, hindering fiber collection. These defects restrict its continuous, large-scale preparation. Summary of the Invention

[0003] The purpose of this invention is to provide a method for preparing sodium alginate / bacterial cellulose composite aerogel fiber and its application, for preparing a novel aerogel long fiber.

[0004] The technical solution adopted in this invention is as follows:

[0005] In a first aspect, the present invention provides a method for preparing sodium alginate / bacterial cellulose composite aerogel fibers, comprising the following steps:

[0006] Step 1: Immerse the bacterial cellulose hydrogel in NaOH aqueous solution and perform alkaline treatment under heating conditions; then wash with water until neutral.

[0007] Step 2: The bacterial cellulose hydrogel treated in Step 1 is pulped and centrifuged to reduce the water content, thus obtaining a bacterial cellulose slurry. Next, water is added to adjust the concentration of the bacterial cellulose slurry. Then, oxidation treatment is carried out: 2,2,6,6-tetramethylpiperidine oxide, sodium bromide, and sodium hypochlorite are added under stirring conditions. Then, NaOH aqueous solution is added dropwise to adjust the pH of the reaction system to between 10 and 10.5, and the reaction is timed. After the reaction is completed, deionized water is added and centrifuged until the supernatant is neutral to obtain the oxidized bacterial cellulose dispersion.

[0008] Step 3: Add sodium alginate to the bacterial cellulose dispersion prepared in Step 2 to prepare a sodium alginate / oxidized bacterial cellulose spinning solution.

[0009] Step 4: Using a syringe, the sodium alginate / oxidized bacterial cellulose spinning solution prepared in step 3 is shaped through a tube and injected into a coagulation bath for gelation to obtain sodium alginate / bacterial cellulose composite hydrogel fiber; the coagulation bath is an aqueous solution of CaCl2.

[0010] Step 5: Replace the sodium alginate / bacterial cellulose composite hydrogel fiber obtained in step 4 with anhydrous ethanol, and then dry it with supercritical carbon dioxide fluid to obtain sodium alginate / bacterial cellulose composite aerogel fiber.

[0011] Step 6: Silanization modification of the sodium alginate / bacterial cellulose composite aerogel fiber obtained in step 5 to obtain radially highly elastic sodium alginate / bacterial cellulose composite aerogel fiber; the modifier used is deionized water and methyltrimethoxysilane.

[0012] In one specific embodiment, in step 1, the bacterial cellulose hydrogel is soaked in a 4% (w / w) NaOH aqueous solution and then heated in an oil bath at a constant temperature of 90°C for 4 hours. o C.

[0013] In one specific embodiment, in step 2, water is added to adjust the concentration of bacterial cellulose slurry to 0.01 g / mL; a 4% NaOH aqueous solution is added dropwise to adjust the pH of the reaction system; and the reaction is timed for 1 h.

[0014] In one specific embodiment, in step 3, the mass ratio of sodium alginate to bacterial cellulose dispersion is 2:1-5.

[0015] Preferably, in step 3, the mass ratio of sodium alginate to bacterial cellulose dispersion is 2:3.

[0016] In one specific embodiment, in step 4, the coagulation bath is a 2% (by mass) CaCl2 aqueous solution.

[0017] In one specific embodiment, in step 5, supercritical carbon dioxide fluid is used to dry the material for 8 hours, wherein the temperature of the supercritical carbon dioxide fluid is 50°C. o C, with a pressure of 15 MPa.

[0018] In one specific embodiment, the specific operation method of step 6 is as follows: The sodium alginate / bacterial cellulose composite aerogel fiber obtained in step 5 is placed together with two centrifuge tubes into a desiccator. The two centrifuge tubes contain 0.8 mL of deionized water and 1 mL of methyltrimethoxysilane, respectively. Then, the desiccator is placed in a 70°C container. o Modify in a constant temperature oven at C for 6-10 hours.

[0019] Preferably, in step 6, the silanization modification time is 8 hours.

[0020] Secondly, the present invention provides an application of sodium alginate / bacterial cellulose composite aerogel fiber, which is used as a clothing fabric.

[0021] The beneficial effects of this invention are as follows: This invention provides a method for preparing sodium alginate / bacterial cellulose composite aerogel fibers and their applications. The aerogel long fibers prepared by this invention have a complex three-dimensional network skeleton. Through testing, the aerogel long fibers prepared by this invention have a length as high as 305 μm. 2 The composite aerogel fiber prepared using this invention possesses a high specific surface area ( / g) and its pore size is mainly distributed in the 30-40 nm range. This characteristic enables the composite aerogel fiber to be woven into textiles with high thermal insulation properties. Its weavability was verified through knotting tests and actual weaving. The excellent radial elasticity of the composite aerogel fiber was verified through radial compression-rebound tests. Thermal insulation performance tests verified that textiles woven from the composite aerogel fiber of this invention have stable thermal insulation capabilities. Based on the above properties, the composite aerogel fiber of this invention can be used as clothing fabric. Attached Figure Description

[0022] Figure 1 This is a comparison diagram of the bacterial cellulose dispersion effect before and after oxidation treatment in Example 1 of the present invention.

[0023] Figure 2 The diagram shown is a connection diagram of the equipment for wet spinning according to the present invention.

[0024] Figure 3 The image shown is a physical picture of the sodium alginate / bacterial cellulose composite hydrogel fiber prepared in Example 1 of the present invention.

[0025] Figure 4 The image shown is a physical picture of the sodium alginate / bacterial cellulose composite aerogel fiber prepared in batches according to the present invention.

[0026] Figure 5 The image shown is a cross-sectional scanning electron microscope image of the sodium alginate / bacterial cellulose composite aerogel fiber prepared in this invention.

[0027] Figure 6 The figure shown is a graph of the results of physical adsorption analysis of the sodium alginate / bacterial cellulose composite aerogel fiber prepared in this invention.

[0028] Figure 7 The diagram shows the knotting test process of the composite aerogel fiber prepared according to the present invention.

[0029] Figure 8 The image shown is a demonstration of how the composite aerogel fibers of this invention are woven into Chinese knots and butterfly shapes.

[0030] Figure 9 The figure shown is a compression-rebound test result of the composite aerogel fiber prepared in this invention.

[0031] Figure 10 The figure shown is a test result of the composite aerogel fiber of the present invention undergoing 30 compression cycles under 80% compression conditions.

[0032] Figure 11 This is a photograph of a textile woven from the composite aerogel fiber of this invention.

[0033] Figure 12 The figure shown is a diagram of the results of three heating-cooling experiments on the textile of this invention.

[0034] Figure 13 The image shown is an infrared thermal image of various textiles when worn on the human body.

[0035] Figure 14 The image shows scanning electron microscope (SEM) images of the three products prepared in Experiment 1 and the product obtained in Example 1.

[0036] Figure 15 The figure shown is a graph of the results of physical adsorption testing of four types of aerogel fibers in Experiment 1 of this invention.

[0037] Figure 16 The figure shown is a graph of the radial compression performance test results of four types of fibers in Experiment 1.

[0038] Figure 17 The figure shown is a graph of the toughness test results for the four types of fibers in Experiment 1.

[0039] Figure 18 The image shows textiles made from four different fibers in Experiment 1 at 90°C. o Infrared thermal image of the hot plate of C.

[0040] Figure 19 The figure shown is a graph of the radial compression performance test results of the two products in Experiment 2 and the product prepared in Example 1.

[0041] Figure 20 The figure shown is a toughness test result graph of the two products in Experiment 2 and the product prepared in Example 1.

[0042] Figure 21 The figure shown is a graph of the mechanical property test results for the three products in Experiment 3. Detailed Implementation

[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] Table 1. Summary of the main performance indicators and sources of the main raw materials and reagents of this invention. Reagent Name source Relevant parameters Bacterial cellulose hydrogel Guilin Sailuna Technology Co., Ltd. Solid content: 1% Sodium alginate Shanghai McLean Biochemical Technology Co., Ltd. CAS: 9005-38-3 Grade: Reagent Grade (90%) Sodium hypochlorite Shanghai Aladdin Biochemical Technology Co., Ltd. CAS: 7681-52-9 Grade: Analytical purity (6-14%) Sodium bromide Shanghai Aladdin Biochemical Technology Co., Ltd. CAS: 7647-15-6 Grade: Analytical purity (99%) 2,2,6,6-Tetramethylpiperidine oxide (TEMPO) Shanghai Aladdin Biochemical Technology Co., Ltd. CAS: 2564-83-298%

[0045] Example 1: A method for preparing sodium alginate / bacterial cellulose composite aerogel fiber, comprising the following steps:

[0046] Step 1: Immerse the bacterial cellulose hydrogel in NaOH aqueous solution and perform alkaline treatment under heating conditions; then wash with water until neutral.

[0047] In this embodiment, the bacterial cellulose hydrogel was washed with a large amount of deionized water to remove impurities; then it was immersed in a 4% (w / w) NaOH aqueous solution and heated in an oil bath at a constant temperature of 90°C for 4 hours. o C; Finally, remove the bacterial cellulose hydrogel and wash it with deionized water until neutral, then set aside.

[0048] Step 2: The bacterial cellulose hydrogel treated in Step 1 is pulped and centrifuged to reduce the water content, thus obtaining a bacterial cellulose slurry. Next, water is added to adjust the concentration of the bacterial cellulose slurry to 0.01 g / mL. Then, oxidation treatment is carried out: 2,2,6,6-tetramethylpiperidine oxide (TEMPO), sodium bromide (NaBr), and sodium hypochlorite (NaClO) are added under stirring conditions. Then, NaOH aqueous solution is added dropwise to adjust the pH of the reaction system to between 10 and 10.5, and the reaction is timed for 1 h. After the reaction is completed, deionized water is added and centrifuged until the supernatant is neutral to obtain the oxidized bacterial cellulose dispersion.

[0049] In this embodiment, 200 g of the bacterial cellulose hydrogel treated in step 1 was placed in a multi-functional food processor and thoroughly pulped. The pulp was then centrifuged at 10,000 r / min for 10 min. This operation was repeated 4 times to obtain 27 mL of bacterial cellulose pulp with extremely low water content. At this time, the mass of the pulp was 25.19 g.

[0050] Subsequently, three 1 mL portions of the bacterial cellulose slurry were continuously taken and placed in three petri dishes. The three petri dishes were then dried in an oven at 80 °C for 5 h to remove all moisture. The average mass of the three dried cellulose portions was denoted as m1, and after testing and calculation, m1 = 0.0689 g. Therefore, the concentration of the bacterial cellulose slurry prepared in this example is 0.0689 g / mL, denoted as c1.

[0051] 3 mL of the 27 mL slurry was used, leaving 24 mL of slurry, the volume of which is recorded as V1; it is then transferred to a beaker and diluted with water to a concentration of c2 = 0.01 g / mL.

[0052] The calculation method for the amount of water added is as follows: First, according to the formula c1V1=c2V2, we can calculate V2=165.4 mL. Further calculation shows that the volume of water added is V... H2O =V2-V1=165.4-24=141.4 mL.

[0053] After adding water, place the beaker on a magnetic stirrer, add the stir bar and start stirring. While stirring, add 2,2,6,6-tetramethylpiperidine oxide (TEMPO), sodium bromide (NaBr), and sodium hypochlorite (NaClO).

[0054] The amount of TEMPO added is calculated according to the following formula: .

[0055] The amount of NaBr added is calculated according to the following formula: .

[0056] The amount of NaClO added is calculated according to the following formula: .

[0057] After adding all the above reagents, add dropwise a 4% NaOH aqueous solution to adjust the pH of the reaction system to between 10 and 10.5, and then start the reaction for 1 hour.

[0058] After the reaction was complete, large amounts of deionized water were repeatedly added and the mixture was centrifuged until the supernatant was neutral, yielding 27.52 g of the oxidized bacterial cellulose dispersion. At this point, the dispersion effect of the oxidized bacterial cellulose in water was as follows: Figure 1 As shown, Figure 1 This is a comparison of the bacterial cellulose dispersion effect before and after oxidation treatment in Example 1 of the present invention. The left side of the figure shows the effect before oxidation treatment, and the right side shows the effect after oxidation treatment. The comparison shows that the bacterial cellulose dispersion effect after oxidation treatment is significantly better than before oxidation, and the aggregation phenomenon is obvious before oxidation.

[0059] Step 3: Add sodium alginate to the bacterial cellulose dispersion prepared in Step 2 to prepare a sodium alginate / oxidized bacterial cellulose spinning solution.

[0060] In this embodiment, the specific operation method is as follows: Take a beaker, add 3 g of the bacterial cellulose dispersion prepared in step 2, then add 95 mL of deionized water, place the beaker on a magnetic stirrer, add 2 g of sodium alginate under stirring conditions, and stir until completely dissolved. Then, use a CNC ultrasonic cleaner to ultrasonically defoam the solution to obtain a spinning solution with a sodium alginate / oxidized bacterial cellulose mass ratio of 2:3.

[0061] Step 4: Using a syringe, the sodium alginate / oxidized bacterial cellulose spinning solution prepared in Step 3 is shaped through a tube and injected into a coagulation bath for gelation, thereby obtaining sodium alginate / bacterial cellulose composite hydrogel fibers. The coagulation bath is a 2% (w / w) CaCl2 aqueous solution.

[0062] like Figure 2 The diagram shows the equipment connection for the wet spinning process of this invention. In this embodiment, the specific operation method is as follows: A 10 mL syringe is used to draw the spinning solution prepared in step 3. The syringe is installed on an injection pump, and the flow rate of the injection pump is set to 30 mL / h. A 1 mm inner diameter flexible tube with a length of 10 cm is connected to the front end of the syringe. The other end of the flexible tube is immersed in a coagulation bath; the coagulation bath is a 2% (w / w) CaCl2 aqueous solution. The injection pump is started, and the spinning solution flows through the flexible tube into the coagulation bath, where it gels to obtain sodium alginate / bacterial cellulose composite hydrogel fibers. A winding machine can be installed on one side of the coagulation bath. One end of the gelled composite hydrogel fiber is fixed to the roller of the winding machine, and the composite hydrogel fiber is slowly wound up. Figure 3 The image shown is a physical picture of the sodium alginate / bacterial cellulose composite hydrogel fiber prepared in Example 1 of the present invention.

[0063] Step 5: Replace the sodium alginate / bacterial cellulose composite hydrogel fiber obtained in step 4 with anhydrous ethanol, and then dry it with supercritical carbon dioxide fluid to obtain sodium alginate / bacterial cellulose composite aerogel fiber.

[0064] In this embodiment, anhydrous ethanol was used for three replacements, each lasting 12 hours, to ensure that the aqueous phase inside the hydrogel fibers was completely converted to the ethanol phase. Subsequently, it was dried using supercritical carbon dioxide fluid at a temperature of 50°C for 8 hours. o C, with a pressure of 15 MPa.

[0065] Step 6: Silanization modification of the sodium alginate / bacterial cellulose composite aerogel fiber obtained in step 5 to obtain radially highly elastic sodium alginate / bacterial cellulose composite aerogel fiber; the modifier used is deionized water and methyltrimethoxysilane.

[0066] In this embodiment, chemical vapor deposition (CVD) was used to modify (silanization modification) the aerogel fibers. The specific procedure is as follows: The sodium alginate / bacterial cellulose composite aerogel fibers obtained in step 5 were placed in a desiccator along with two centrifuge tubes. Each centrifuge tube contained 0.8 mL of deionized water and 1 mL of methyltrimethoxysilane, respectively. The desiccator was then placed in a 70°C environment. o The aerogel fiber was modified in a constant temperature oven at C for 6 h. This process involves a chemical reaction to form a rigid hydrophobic layer on the surface of the aerogel fiber skeleton, ultimately yielding radially highly elastic sodium alginate / bacterial cellulose composite aerogel fiber.

[0067] like Figure 4 The image shown is a physical picture of the sodium alginate / bacterial cellulose composite aerogel fibers prepared in batches according to the present invention. Testing revealed that the diameter of the sodium alginate / bacterial cellulose composite aerogel fibers prepared in batches according to the present invention is 0.9 mm.

[0068] The microstructure of the sodium alginate / bacterial cellulose composite aerogel fibers prepared in this invention was observed using scanning electron microscopy. Figure 5 The image shown is a cross-sectional scanning electron microscope (SEM) image of the sodium alginate / bacterial cellulose composite aerogel fiber prepared according to this invention. Among them, Figure 5 a is a scanning electron microscope image at the 500 μm scale. Figure 5 b and 5c are scanning electron microscope images at the 4 μm and 1 μm scales, respectively.

[0069] from Figure 5 As can be seen from the above, the sodium alginate / bacterial cellulose composite aerogel fiber prepared by this invention has a complex three-dimensional network skeleton.

[0070] Next, the present invention uses a physical adsorption instrument to test the prepared composite aerogel fibers, measuring their pore size and pore volume. For example... Figure 6 The figure shown is a graph of the results of physical adsorption analysis of the sodium alginate / bacterial cellulose composite aerogel fiber prepared in this invention.

[0071] Test results show that the composite aerogel fiber prepared by this invention has a high density of up to 305 μm. 2 With a high specific surface area of ​​ / g and its pore size mainly distributed in the range of 30~40 nm, which is lower than the mean free path of gas molecules (60~70 nm), the composite aerogel fiber prepared by the present invention can be woven into textiles with high heat retention.

[0072] Subsequently, the prepared composite aerogel fibers were subjected to knotting tests. For example... Figure 7 The image shows the knotting test process of the composite aerogel fiber prepared according to this invention. The left side... Figure 7 Image a shows the composite aerogel fibers before knotting. Figure 7 b is a diagram showing the knotted composite aerogel fibers. Figure 7 c is a diagram showing the composite aerogel fibers after untying. After repeated knotting operations, no obvious creases were observed in the composite aerogel fibers prepared according to this invention.

[0073] To further verify the weavability of the composite aerogel fibers prepared in this invention, the composite aerogel fibers were woven into more complex Chinese knots and butterfly shapes. For example... Figure 8 The image shows examples of how the composite aerogel fibers of this invention are woven into Chinese knots and butterfly shapes. Experimental verification has shown that the composite aerogel fibers prepared by this invention can meet complex weaving requirements.

[0074] To further verify the radial elasticity of the composite aerogel fiber prepared in this invention, a radial compression-rebound test was conducted on it using a universal testing machine. Figure 9 The figure shown is a compression-resilience test result diagram of the composite aerogel fiber prepared in this invention. From... Figure 9 It can be seen that under radial compression of 20%, 40%, 60%, and 80%, no obvious irreversible rebound was observed after the external force was removed.

[0075] Then, a compression cycle test was performed 30 times under 80% compression conditions. Figure 10 The figure shown illustrates the test results of the composite aerogel fiber of the present invention under 30 compression cycles at 80% compression. It demonstrates the excellent radial elasticity of the composite aerogel fiber of the present invention.

[0076] Furthermore, to verify the thermal insulation performance of the composite aerogel fiber textiles, the present invention weaves the prepared composite aerogel fibers into textiles. For example... Figure 11 This is a photograph of a textile woven from the composite aerogel fiber of this invention.

[0077] This invention conducted thermal cycling tests on woven textiles. Specifically, the woven textile was placed on a temperature-variable hot plate, with the hot plate temperature adjusted between room temperature and 110 °C. The temperature of the upper surface of the textile was monitored using thermocouples connected to a data acquisition instrument; changes in the hot plate temperature and the upper surface temperature of the textile were monitored. This invention conducted three heating-cooling experiments, such as... Figure 12The figure shows the results of three heating-cooling experiments on the textile of this invention. As can be seen from the figure, a temperature difference of approximately 35°C was maintained between the textile and the hot plate, which verifies that the textile woven from the composite aerogel fiber of this invention has stable thermal insulation capabilities.

[0078] To verify the thermal insulation performance of the composite aerogel fiber woven textile of the present invention when worn on the human body, the present invention simultaneously wore the composite aerogel fiber woven textile of the present invention, as well as textiles made of cotton and wool, on a person's arm, and observed the temperature difference using infrared thermal imaging. Figure 13 The images shown are infrared thermal images of the textiles when worn on the human body. It can be clearly observed that the surface temperature of the textile woven from the composite aerogel fiber of this invention is lower than that of the other two textiles.

[0079] The above tests demonstrate that the composite aerogel fiber of this invention can be applied in the field of clothing fabrics.

[0080] The present invention further conducted the following single-variable experiments.

[0081] Experiment 1: This experiment investigated the effect of different amounts of oxidizing bacterial cellulose added on the prepared composite aerogel fibers. Based on Example 1, this experiment modified the amounts of bacterial cellulose dispersion and deionized water added in step 3 of Example 1.

[0082] Comparative Experiment 1.1 differs from Example 1 in that the following step 3 is used.

[0083] Take a beaker, add 98 mL of deionized water, place the beaker on a magnetic stirrer, and add 2 g of sodium alginate while stirring until completely dissolved. Then, use a CNC ultrasonic cleaner to ultrasonically defoam the solution, obtaining a spinning solution with a mass fraction of 2% sodium alginate (SA). Bacterial cellulose dispersions were not used in this experiment.

[0084] The remaining operations are the same as in Example 1.

[0085] In comparative experiment 1.2, unlike in example 1, step 3 was performed as follows.

[0086] Take a beaker, add 1 g of the bacterial cellulose dispersion prepared in step 2, then add 97 mL of deionized water. Place the beaker on a magnetic stirrer, and add 2 g of sodium alginate while stirring until completely dissolved. Then, use a CNC ultrasonic cleaner to ultrasonically defoam the solution, obtaining a spinning solution with a sodium alginate / oxidized bacterial cellulose mass ratio of 2:1. The ratio of sodium alginate to bacterial cellulose dispersion is denoted as SA:BC = 2:1.

[0087] The remaining operations are the same as in Example 1.

[0088] Comparative Experiment 1.3 differs from Example 1 in that step 3 is performed as follows.

[0089] Take a beaker, add 5 g of the bacterial cellulose dispersion prepared in step 2, then add 93 mL of deionized water. Place the beaker on a magnetic stirrer, and add 2 g of sodium alginate while stirring until completely dissolved. Then, use a CNC ultrasonic cleaner to ultrasonically defoam the solution, obtaining a spinning solution with a sodium alginate / oxidized bacterial cellulose mass ratio of 2:5. The ratio of sodium alginate to bacterial cellulose dispersion is denoted as SA:BC = 2:5.

[0090] The remaining operations are the same as in Example 1.

[0091] In Example 1, the ratio of sodium alginate to bacterial cellulose dispersion was denoted as SA:BC = 2:3.

[0092] like Figure 14 The image shown is a scanning electron microscope (SEM) image of the three products prepared in Experiment 1 and the product obtained in Example 1. From... Figure 14 As can be seen, all four types of fibers have complex three-dimensional network structures.

[0093] Next, this invention uses a physical adsorption instrument to test four types of composite aerogel fibers, measuring their pore size and pore volume. For example... Figure 15 The image shown is a graph illustrating the results of physical adsorption analysis of the four aerogel fibers in Experiment 1 of this invention. The results indicate that all four fibers exhibit the high specific surface area characteristic of aerogels, and their pore sizes all fall within the mesoporous range.

[0094] Subsequently, the present invention used a universal testing machine to test the radial compression properties and toughness of the four fibers, such as... Figure 16 The figure shown is a graph of the radial compression performance test results of four types of fibers in Experiment 1. Figure 17 The image shown is a graph depicting the toughness test results of the four types of fibers in Experiment 1. From... Figure 16 , 17 As can be seen, when SA:BC=2:3, the composite aerogel fiber has the best radial elasticity and toughness.

[0095] The present invention then weaves the four fibers into textiles in the same manner and places them at 90°C. o Infrared thermal imaging is performed on the hot plate of C, such as Figure 18 The image shows textiles made from four different fibers in Experiment 1 at 90°C. o Infrared thermal imaging of a hot plate (C). It can be observed that the upper surface temperature of textiles woven from fibers prepared by mixing sodium alginate and bacterial cellulose dispersion in a 2:3 ratio is significantly lower than that of other woven fabrics.

[0096] Experiment 2: This experiment investigated the effect of sodium alginate dosage on the product. Based on Example 1, this experiment modified the amounts of sodium alginate and deionized water added in step 3 of Example 1.

[0097] Comparative Experiment 2.1 differs from Example 1 in that the following step 3 is used.

[0098] Take a beaker, add 3g of the bacterial cellulose dispersion prepared in step 2, then add 96 mL of deionized water. Place the beaker on a magnetic stirrer, and add 1g of sodium alginate while stirring until completely dissolved. Then, use a CNC ultrasonic cleaner to ultrasonically defoam the solution, obtaining a spinning solution with a sodium alginate / oxidized bacterial cellulose mass ratio of 1:3. The ratio of sodium alginate to bacterial cellulose dispersion is denoted as SA:BC = 1:3.

[0099] The remaining operations are the same as in Example 1.

[0100] Comparative Experiment 2.2 differs from Example 1 in that the following step 3 is used.

[0101] Take a beaker, add 3g of the bacterial cellulose dispersion prepared in step 2, then add 94 mL of deionized water. Place the beaker on a magnetic stirrer, and add 3g of sodium alginate while stirring until completely dissolved. Then, use a CNC ultrasonic cleaner to defoam the solution, obtaining a spinning solution with a sodium alginate / oxidized bacterial cellulose mass ratio of 1:1. The ratio of sodium alginate to bacterial cellulose dispersion is denoted as SA:BC = 1:1.

[0102] The remaining operations are the same as in Example 1.

[0103] The mechanical properties of the two products in Experiment 2 were tested using a universal testing machine, and compared with those of the product prepared in Example 1. Figure 19 The figure shown is a graph of the radial compression performance test results of the two products in Experiment 2 and the product prepared in Example 1. Figure 20 The figure shows the toughness test results of the two products in Experiment 2 and the product prepared in Example 1. As can be seen from the figure, the radial compression rebound and axial tensile strength of the sodium alginate / bacterial cellulose mass ratio of 2:3 are better than those of the other two ratios.

[0104] Experiment 3: This experiment investigates the effect of silanization modification time in step 6 of Example 1 on the product.

[0105] Specifically, the aerogel fibers obtained in step 5 of Example 1 were evenly divided into three portions, and the silanization modification operation in step 6 was performed on each portion for 6, 8, and 10 hours, respectively. After modification, their mechanical properties were tested. The products were designated as CVD6h, CVD8h, and CVD10h, respectively.

[0106] like Figure 21 The figure shows the mechanical property test results of the three products in Experiment 3. It can be clearly seen from the figure that the radial elasticity of the sample modified for 8 hours is better than that of the other times. This indicates that the radial elasticity increases with the extension of the modification time. However, when the modification time is too long, the rigidity inside the aerogel fiber becomes too large, its brittleness increases, and its radial elasticity decreases, making it unsuitable for use as clothing fabric.

[0107] It is understood that the present invention has been described through some embodiments, and those skilled in the art will recognize that various changes or equivalent substitutions can be made to these features and embodiments without departing from the spirit and scope of the invention. Furthermore, under the teachings of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the protection scope of the present invention.

Claims

1. A method for preparing sodium alginate / bacterial cellulose composite aerogel fiber, characterized in that, Includes the following steps: Step 1: Immerse the bacterial cellulose hydrogel in NaOH aqueous solution and perform alkaline treatment under heating conditions; then wash with water until neutral. Step 2: The bacterial cellulose hydrogel treated in Step 1 is pulped and centrifuged to reduce its water content, thus obtaining a bacterial cellulose slurry. Next, water is added to adjust the concentration of the bacterial cellulose slurry. Then, an oxidation treatment is performed: 2,2,6,6-tetramethylpiperidine oxide, sodium bromide, and sodium hypochlorite are added under stirring conditions. Then, NaOH aqueous solution is added dropwise to adjust the pH of the reaction system to between 10 and 10.5, and the reaction is timed. After the reaction is complete, deionized water is added and the mixture is centrifuged until the supernatant is neutral, obtaining the oxidized bacterial cellulose dispersion. Step 3: Add sodium alginate to the bacterial cellulose dispersion prepared in Step 2 to prepare a sodium alginate / oxidized bacterial cellulose spinning solution. Step 4: Using a syringe, the sodium alginate / oxidized bacterial cellulose spinning solution prepared in Step 3 is shaped through a tube and injected into a coagulation bath for gelation to obtain sodium alginate / bacterial cellulose composite hydrogel fiber; the coagulation bath is an aqueous solution of CaCl2. Step 5: Replace the sodium alginate / bacterial cellulose composite hydrogel fiber obtained in step 4 with anhydrous ethanol, and then dry it with supercritical carbon dioxide fluid to obtain sodium alginate / bacterial cellulose composite aerogel fiber. Step 6: Silanization modification of the sodium alginate / bacterial cellulose composite aerogel fiber obtained in step 5 to obtain sodium alginate / bacterial cellulose composite aerogel fiber; the modifier used is deionized water and methyltrimethoxysilane.

2. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 1, characterized in that, In step 1, the bacterial cellulose hydrogel was soaked in a 4% (w / w) NaOH aqueous solution and then heated in an oil bath at a constant temperature of 90°C for 4 hours. o C.

3. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 1, characterized in that, In step 2, water was added to adjust the concentration of bacterial cellulose slurry to 0.01 g / mL; a 4% NaOH aqueous solution was added dropwise to adjust the pH of the reaction system; and the reaction was timed for 1 h.

4. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 1, characterized in that, In step 3, the mass ratio of sodium alginate to bacterial cellulose dispersion is 2:1-5.

5. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 4, characterized in that, In step 3, the mass ratio of sodium alginate to bacterial cellulose dispersion is 2:

3.

6. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 1, characterized in that, In step 4, the coagulation bath is a 2% (w / w) CaCl2 aqueous solution.

7. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 1, characterized in that, In step 5, the material is dried using supercritical carbon dioxide fluid for 8 hours, wherein the temperature of the supercritical carbon dioxide fluid is 50°C. o C, with a pressure of 15 MPa.

8. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 1, characterized in that, The specific operation method for step 6 is as follows: Place the sodium alginate / bacterial cellulose composite aerogel fiber obtained in step 5 into a desiccator along with two centrifuge tubes. Each centrifuge tube contains 0.8 mL of deionized water and 1 mL of methyltrimethoxysilane, respectively. Then, place the desiccator into a 70°C container. o Modify in a constant temperature oven at C for 6-10 hours.

9. The method for preparing sodium alginate / bacterial cellulose composite aerogel fiber according to claim 7, characterized in that, In step 6, the silanization modification time is 8 hours.

10. An application of a sodium alginate / bacterial cellulose composite aerogel fiber, characterized in that, The sodium alginate / bacterial cellulose composite aerogel fiber described in claim 1 is used as a clothing fabric.

Citation Information

Patent Citations

  • Radially highly elastic aerogel fibers and applications thereof

    CN121065856B